Geological evidence of a palynologically defined cooling in southeastern Canada at 10 000-8000 14C yr BP - Brookes, Ian; Grant, Douglas (Géographie physique et Quaternaire, 2007)
AbstractPost-glacial pollen spectra over a wide area of southeastern Canada have been interpreted as showing that the general warmth-adapted trend of regional vegetation change was interrupted between 10 000 and 8000 14C yr BP, reverting to conditions associated with a markedly cooler climate. This biotic reversal has been attributed to a climatic cooling caused by discharge of frigid water from glacial Lake Agassiz, through the Great Lakes to the Goldthwait Sea in the Gulf of St. Lawrence basin. Here, we assemble geological evidence from widely scattered localities in and around the Gulf of St. Lawrence, all previously reported, a majority unexplained, and ascribe it collectively to the same climatic cooling. We interpret the marine diamicts and other faunal reversals as the products of cooling, which intensified sea-ice conditions during the interval 10 000-8000 14C yr BP, specifically at 9300 14C yr (9170 yr, reservoir corrected), conditions resulting from that meltwater influx. This age was several centuries too young to be correlated with the Preboreal Oscillation, but several easterly overflows of Lake Agassiz occurred before and after this date, and may have increased sea-ice in the Goldthwait Sea, singly or by hysteresis. Other truly glacial features in southeastern Canada, such as moraine systems and diamictons, are also referred to this cooling.